Cryptic speciation in the Merodon luteomaculatus complex (Diptera: Syrphidae) from the eastern Mediterranean. (16th October 2017) - Radenković, Snežana; Šašić Zorić, Ljiljana; Djan, Mihajla; Obreht Vidaković, Dragana; Ačanski, Jelena; Ståhls, Gunilla; Veličković, Nevena; Markov, Zlata; Petanidou, Theodora; Kočiš Tubić, Nataša; Vujić, Ante
Abstract: The Merodon aureus group is characterized by high endemism and the presence of morphologically cryptic species. Within one of its subgroups, M . bessarabicus, seven species and four more species complexes have been described to date. One of these complexes, the M . luteomaculatus, comprises new taxa that are the subject of the present study. Its members have allopatric ranges restricted to the Balkan Peninsula and Aegean islands. This complex exhibits morphological variability that could not be characterized using a traditional morphological approach. Thus, we used integrative taxonomy with independent character sets (molecular, geometric morphometric, distributional) to delimit species boundaries. Data on three molecular markers ( COI, 28S rRNA, and ISSR) and geometric morphometry of the wing and male genitalia, together with distributional data, enabled recognition of six cryptic species within the complex: M . andriotes sp. n., M . euri sp. n., M . erymanthius sp. n., M . luteomaculatus sp. n., M . naxius sp. n., and M . peloponnesius sp. n. We discuss the possible influence of Aegean paleogeographical history on the speciation of this complex. Abstract : The Merodon luteomaculatus complex comprises new taxa with allopatric ranges restricted to the Balkan Peninsula and Aegean islands. This complex exhibits morphological variability that could not be characterized using a traditional morphological approach. However, integrative taxonomy enabled recognition of six cryptic species within the complex: M . andriotes sp. n., M . euri sp. n., M . erymanthius sp. n., M . luteomaculatus sp. n., M . naxius sp. n., and M . peloponnesius sp. n. The speciation was possibly influenced by Aegean paleogeographical history.